A study of the durability of concrete reinforced with hemp fibers exposed to external Sulfatic attack - Ziane, Sami; Khelifa, Mohammed-Rissel; Mezhoud, Samy (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The purpose of this paper is to study the durability of concrete reinforced with hemp fibers in the face of external Sulfatic attack. For this purpose, five types of concrete were formulated; three types of concrete reinforced with hemp fibers (HC-0.25, HC-0.5, and HC-1) at 0.25%, 0.5%, and 1% of hemp fibers in volume, respectively. And two control concretes, being ordinary concrete (OC) and polypropylene fiber reinforced concrete (PC).
Keywords: reinforced concrete; hemp fibers; polypropylene fibre; mechanical performance; test durability; sulfatic attacks; beton zbrojony; włókna konopne; włókna polipropylenowe; właściwości mechaniczne; badanie trwałości; siarczany